The Social Construction of a Reading (Dis)Ability. Issue 3 (23rd January 2016) - Kabuto, Bobbie
Abstract: This article highlights one mother–son case study that was part of a larger study, Revaluing Readers and Families (Kabuto, 2009, 2015 ). Here the author focuses on how the mother, Terry, interpreted her 7‐year‐old son Peter's oral reading performances and how her interpretation led her to construct a label around a reading disability. Study data include interviews, observations of parent–child interactions, oral readings and retellings, and family retrospective miscue analysis. Data were analyzed using miscue analysis procedures to examine reading behaviors and also discourse analysis to study how language mediated the construction of and defended the culture of a reading disability within the family. Framed by a sociocultural‐historical theoretical foundation, the findings illustrate how Terry interpreted Peter's reading ability within a transgenerational space, which is a convergence zone so the past, present, and future come together to create a new space, or a living cultural space, that transcends the immediate moment. Results and findings from this mother–son case study question the nature and root of Peter's struggles with reading, moving it from being localized in the person to being a part of a social matrix defining a culture for the family. The author concludes by revisiting the concept of reading ability and addressing the implications of this research.